HUBUNGAN TUPOKSI DINAS PARIWISATA KEBUDAYAAN PEMUDA DAN OLAHRAGA DENGAN PEMBINAAN OLAHRAGA PRESTASI - Edison Hermanus Womsiwor; Habibi Sutirta (Journal of Physical Education and Sport Science, 2020)
The lack of sports performance coaching has an impact on the competitiveness of Mimika Regency athletes at the regional, national and international levels. In general, they are still unable to show proud achievements and are far below other regions in Indonesia, this is the background of this research. This study aims to: 1) To determine the extent to which the role of the Mimika Regency Youth and Sports Service (Dispora) in carrying out its duties and functions, namely developing sports achievements in Mimika Regency, 2) To determine the extent to which the Youth and Sports Service (Dispora) has contributed positive development in the field of sports through the nursery and guidance program for talented athletes in Mimika district, 3) To determine the extent of the relationship between the main duties and functions of the youth service and sports in Mimika district with the development of sports achievement in Mimika district. This research uses quantitative research methods with a descriptive approach. The results of this study indicate that: There is a significant relationship between the Tupoksi variable of the Youth and Sports Service on the development of achievement sports in Mimika Regency, with the level of correlation which refers to a significance value of 0.010 or it can be interpreted that 10% is influenced by the variable tupoksi of the District Youth and Sports Service. Mimika towards coaching achievement sports in Mimika Regency and 90% is influenced by other factors.